Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1093/ajh/4.9.773
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Insulin and Lipid Metabolism in Milan Hypertensive Rats

Abstract: Plasma glucose, insulin, triglyceride, and cholesterol concentrations were measured in male rats of the Milan hypertensive strain (MHS) and compared to the Milan normotensive strain (MNS) of the same body weight. Both blood pressure (P less than .001) and left ventricular weight (P less than .005) were higher in rats of the MHS. Although plasma glucose concentrations were similar in both groups, mean (+/- SEM) plasma insulin concentration were significantly higher (P less than .01) in MHS as compared to MNS ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…In summary, we have mapped QTLs regulating selected cholesterol and phospholipid phenotypes in the rat to regions of chromosomes 8,19, and 20 that are suspected to contain genes regulating blood pressure. These findings are consistent with the suggestion that lipid levels and blood pressure may be modulated by linked genes or perhaps even the same genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we have mapped QTLs regulating selected cholesterol and phospholipid phenotypes in the rat to regions of chromosomes 8,19, and 20 that are suspected to contain genes regulating blood pressure. These findings are consistent with the suggestion that lipid levels and blood pressure may be modulated by linked genes or perhaps even the same genes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is hoped that studies of animal models might shed light on genetic mechanisms underlying dyslipidemia and high blood pressure. Recent studies have suggested that increased blood pressure may be associated with disorders of lipid and or insulin metabolism in several animal models of hypertension including the spontaneously hypertensive rat (SHR) (6), the Dahl salt-sensitive rat (7), the Milan rat (8), the Lyon rat (9), and the fructose fed rat (10). Thus, rodent models might be useful for investigating whether genes regulating blood pressure are linked to genes influencing lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…1998;32:235-242. )Key Words: hyperinsulinemia Ⅲ insulin resistance Ⅲ losartan Ⅲ PD123319 Ⅲ angiotensin receptor antagonist N umerous clinical and epidemiological studies have demonstrated that essential hypertension is correlated with insulin resistance and hyperinsulinemia.1-3 The close association between hypertension and insulin resistance-hyperinsulinemia has been noted to occur in some genetically hypertensive rat models, such as spontaneously hypertensive rats, 4,5 Milan hypertensive rats, 6 and Dahl salt-sensitive rats. …”
mentioning
confidence: 99%
“…1-3 The close association between hypertension and insulin resistance-hyperinsulinemia has been noted to occur in some genetically hypertensive rat models, such as spontaneously hypertensive rats, 4,5 Milan hypertensive rats, 6 and Dahl salt-sensitive rats.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Sustained high carbohydrate feeding in rats results in hypertension that is also correlated with insulin resistance and hyperinsulinemia. [7][8][9] Moreover, we and others have demonstrated that long-term insulin administration causes hypertension in rats.…”
mentioning
confidence: 99%